AL-QUR’AN DAN ISLAMISASI BAHASA ARAB - Rahmat Hidayat (STIQ al-Lathifiyyah Palembang, 2019)
Al Qur’an was sent down to Prophet Muhammad SAW as the Holy book by Arabic. Allah decided Arabic as one of miracles because it was the pure language and uninfluenced by any concept, philoshopy of religion, and doctrines by other cultures; and also built by a great roof of words with eternally semantic guarded purity. In Jahiliyah, Arabic was stated as sastra language. It was changed as a science of language since itwas sent down as wahyu. By this case, author decided that process (the alteration from sastra to be wahyu) is a part of Islamization process. The terms, definitions, and new key words come from Islamization process. Those concepts gave new sense which was different in using and understanding before Al qur’an was sent down. Islamization Arabic, worldview, and framework of the society were changed into Islamic substance.